Early Education from Birth to Age 3: Three Analylitical Perspectives - Ramírez-Abrahams, Patricia; Patiño-Mora, Vivian; Gamboa-Vásquez, Elsa (Revista Electrónica Educare, 2014)
This paper shows the results of a diagnostic study conducted to learn the perceptions and opinions of a group of educators, families and child care centers about formal education during the first three years of life. The paper includes the pedagogic principles and practices considered important by the participants regarding attention, education and care for children 3 and younger. A qualitative approach was used to carry out the research because it allowed knowing the participants’ impressions and thoughts related to early education. Participants included pre-school and special education teachers with early stimulation expertise, families whose children were 0 to 3 years and child care centers that offer attention, education and care services for the aforementioned ages. The information was gathered through observation in the centers along with other instruments such as questionnaires and an observation guide with field notes. Data analysis has a descriptive scope and data triangulation of results is used to validate the study. Among the main conclusions it is determined that the educators, families and child care centers observed agree that quality affective and cognitive relations must be a priority within this age range. In addition, the educational environment must allow for the child’s development focusing on principles such as respect for his/her individual learning pace and daily life. This paper contributes to formulate pedagogic proposals for the education of children ages 0 to 3.